Strategi Komunikasi Mahasiswa Institut Agama Islam - Illananingtyas, Tenika (Proceedings of Annual Conference for Muslim Scholars, 2019)
The difficulties faced by the students of Islamic Institute when they learn in speaking class. In their presentation or talk as performance, they have lack for delivering idea. There are difficulties of the foreign language owing to their hesitation and unfamiliar of vocabulary. Meanwhile, they have to present ideas as performance to the audiences. Thus, when facing that problem, it is needed a strategy which can solve their difficulty. Communication strategy can be used when they faced difficulties in speaking. The students’ attempts strategies in communication which can make the utterances can be understandable and meaningful for achieving communication goal. In addition, the communication strategy is crucial way which can be implemented in the teaching speaking. This paper concerns on the kinds of communication strategies used by the students of Islamic Institute and the process of communication strategy in the speaking class. The descriptive study is conducted in this study since the data are collected are in the form of word. Finally, the result of this study can give new insight for the teachers that communication strategy can be used not only for daily communication but for also teaching speaking